The dynamics of traditional gold mining on customary land: Between local wisdom and the pressure of illegal gold mining - Nurafni, Melia; Siregar, Yusni Ihwan; Suwondo, Suwondo; Gusliana , HB (Journal of Degraded and Mining Lands Management, 2026)
Customary land is an essential asset for indigenous communities and a primary source of livelihood. In recent years, however, traditional gold mining has become increasingly threatened by the emergence of artisanal and small-scale gold mining (ASGM) activities within customary areas. This study aimed to analyse the dynamics of traditional gold mining on customary land and to examine the local wisdom values that support conservation. Data were collected through observation and in-depth interviews. Changes in land cover were measured using the area calculation method through post-classification area statistics techniques in a Geographic Information System (GIS), and the data were analysed using qualitative descriptive methods. The findings showed that: (1) the utilization of customary land for traditional gold mining has progressively declined as a result of land-use conversion. The dynamics experienced by the Indigenous community illustrate a process of commons enclosure, in which customary land as a communal resource has increasingly been transformed into privatized or commercialized space through rental mechanisms, thereby causing traditional gold panners to lose access to their customary living and working spaces; and (2) local wisdom practices embedded in traditional gold panning contribute to ecosystem conservation. These values include: (a) the philosophy of “not being greedy,” (b) the use of simple technology, namely wooden pans (ethno-technology), (c) shallow surface excavation, (d) gold separation through the panning motion without mercury, and (e) a subsistence-oriented ethic associated with gold panning as a livelihood source.